2011
DOI: 10.1007/s00044-011-9631-3
|View full text |Cite
|
Sign up to set email alerts
|

Indazole: a medicinally important heterocyclic moiety

Abstract: This article reveals the various biological activities of the heterocyclic compound, indazole, including anti-inflammatory, antimicrobial, antiHIV, anticancer, hypoglycemic, antiprotozoal, antihypertensive, and other activities. From the observed biological activities of the indazole moiety, it is concluded that the medicinal properties of indazole have to be explored in the near future for the treatment of various pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(60 citation statements)
references
References 50 publications
0
58
0
1
Order By: Relevance
“…23) We anticipated that benzophenone tosylhydrazone 6a would undergo intramolecular C-H amination with the aid of a palladium catalyst to afford 3-substituted indazoles 7a. 24) Through the systematic screenings of a range of palladium sources, reoxidants, and solvents, we found that the desired cyclization did occur in dimethyl sulfoxide (DMSO) at 50°C in the presence of a catalytic amount of Pd(OAc) 2 along with Cu(OAc) 2 as a reoxidant.…”
Section: )mentioning
confidence: 99%
“…23) We anticipated that benzophenone tosylhydrazone 6a would undergo intramolecular C-H amination with the aid of a palladium catalyst to afford 3-substituted indazoles 7a. 24) Through the systematic screenings of a range of palladium sources, reoxidants, and solvents, we found that the desired cyclization did occur in dimethyl sulfoxide (DMSO) at 50°C in the presence of a catalytic amount of Pd(OAc) 2 along with Cu(OAc) 2 as a reoxidant.…”
Section: )mentioning
confidence: 99%
“…1 The manipulation of substitution pattern is crucial for designing pharmaceutical molecules bearing indazoles. We are interested in the introduction of a pyridinyl alkyl group into indazoles because some pyridinyl alkyl indazoles have shown important biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…This ring system serves as a core component of important nitrogen containing heterocycles that display a broad range of biological properties, such as the inhibition of nitric oxide 1 and HIV protease, 2 anti-inflammatory, 3 antitumor, 4 and anti-cancer 5 activities, and serotonin 5-HT3 receptor antagonist behavior. This ring system serves as a core component of important nitrogen containing heterocycles that display a broad range of biological properties, such as the inhibition of nitric oxide 1 and HIV protease, 2 anti-inflammatory, 3 antitumor, 4 and anti-cancer 5 activities, and serotonin 5-HT3 receptor antagonist behavior.…”
Section: Introductionmentioning
confidence: 99%